2018
DOI: 10.1186/s13046-018-0764-9
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of TGFBR2 expression and tumour progression in prostate cancer involve diverse hypoxia-regulated pathways

Abstract: BackgroundDysregulation of transforming growth factor β (TGF-β) signaling and hypoxic microenvironment have respectively been reported to be involved in disease progression in malignancies of prostate. Emerging evidence indicates that downregulation of TGFBR2, a pivotal regulator of TGF-β signaling, may contribute to carcinogenesis and progression of prostate cancer (PCa). However, the biological function and regulatory mechanism of TGFBR2 in PCa remain poorly understood. In this study, we propose to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
5
25
0
Order By: Relevance
“…To further evidence that the increased expression of miR‐210 is associated with hypoxia in clinical samples, we examined expression of various hypoxia‐related genes in a well‐characterized TCGA dataset ( n = 330). This showed that EZH2 , another marker of prostate tumour hypoxia (Zhou et al, 2018), has a strong positive correlation with miR‐210 expression in these samples (Figure 3f). Likewise, the hypoxia‐induced genes SPP1 and DLGAP5 , which code for ostepontin and HURP proteins respectively, also show significant positive correlation with clinic‐pathological parameters of prostate cancer progression (Figure S2).…”
Section: Resultsmentioning
confidence: 75%
“…To further evidence that the increased expression of miR‐210 is associated with hypoxia in clinical samples, we examined expression of various hypoxia‐related genes in a well‐characterized TCGA dataset ( n = 330). This showed that EZH2 , another marker of prostate tumour hypoxia (Zhou et al, 2018), has a strong positive correlation with miR‐210 expression in these samples (Figure 3f). Likewise, the hypoxia‐induced genes SPP1 and DLGAP5 , which code for ostepontin and HURP proteins respectively, also show significant positive correlation with clinic‐pathological parameters of prostate cancer progression (Figure S2).…”
Section: Resultsmentioning
confidence: 75%
“…Therefore, other modulators may regulate TGFBR2 at the mRNA level. For example, the H3K27 methyltransferase enzyme EZH2 contributes to TGFBR2 silencing by promoter hypermethylation in prostate cancer . Moreover, miR‐93 and miR‐204 , which are aberrantly expressed in various malignant tumors, including prostate and breast cancers, respectively, regulate cancer progression by targeting TGFBR2 .…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of prostate cancer cells to TGF-β-mediated growth inhibition is thus possibly a result of decreased expression of TGFBR2, which acts as a tumor suppressor gene [237,238]. Downregulation of TGFBR2 in PCa cells might result from hypoxic activation of DNA methyltransferases, which leads to the hypermethylation of the promoter region of TGFBR2 [239]. Contrarily, earlier research reported a lack of promoter methylation and mutations in the TGFBR2 gene [240].…”
Section: Prostate Cancermentioning
confidence: 96%
“…The expression of miR-93 is increased in prostate tumors compared with non-tumorous control samples and correlates with cancer progression. Transfection of prostate cancer cell lines with miR-93 mimics stimulates their proliferation, migration, and invasion [239]. Complex regulation of the TGF-β signaling pathway is exerted by miR-34b, which modulates expressions of TGF-β, TGFBR1, and pSMAD4, p53.…”
Section: Prostate Cancermentioning
confidence: 99%